Location of Cynological Units in the Structure of the National Police of Ukraine and in the System of the Ministry of the Internal Affairs - V. V. Garmash (Law and Safety)
The study was aimed at improving the legal support of the activities of police cynologists. For what was analyzed the current state of the legal framework that provides the activities of the canine units of the National Police of Ukraine (NPU), considered the historical features of the development of the canine service in the system of bodies subordinate to the Ministry of Internal Affairs (MIA). Today, police cynologists are demonstrating tangible service results, confirming the effectiveness of cynology as a powerful tool for law enforcement agencies. However, most researchers agree on the need to improve dog training in OBC, which is the relevance of this study. As a result of the analysis, the main stages of the development of cynology were distinguished, from the beginning of its birth in the world, the formation in the domestic power structures and until it acquired a modern state. The structure of the canine units of the National Police of Ukraine is characterized. The description is given of the place occupied by the canine services in the system of the Ministry of Internal Affairs of Ukraine. Compared to the terms “canine service” and “canine units”, the scope of their application is outlined. The changes in the legal support to the activities of police cynologists caused by the reform of the Ukrainian police are considered. The vector development of canine services has been focused on European standards and the role of the Concept calculated by 2020 has been highlighted as a new tool for managing related processes. The analysis of the regulatory base of official cynology of the NPS revealed the expediency of more active development of its methodological component. As conclusions with practical application, it is proposed to use the methodological base worked out by the police of Ukraine (after all, the practical methods of using service dogs for the most part have not changed). When introducing new developments, special attention should be paid to the contemporary challenges of the criminogenic situation (such as explosives, weapons, drugs).